Reading Anna’s Instability and Fear of Abandonment in Anna Karenina - Diva Wenanda (Universitas Airlangga, 2022)
Literary works often represent psychological issues through the conflicts they pose. Every so often, most literary works cannot be grasped as purely a psycho-literary works, but rather they implicitly connote psychological themes through conflicts, characterizations, and even settings. In continuing this tradition, this study examines a classic literature by Leo Tolstoy entitled Anna Karenina. This literary work is often seen to be an allegory for Imperial Russian community, social unrest, betrayal, and familial problems. Expanding the rich themes of this novel, this study specifically analyzes Anna Karenina through psychological lens. Concept of Borderline Personality Disorder (BPD) by Susan Hoeksema is used as the main concept to interpret the findings of the analysis. This study used qualitative method through a closed-reading attempt. The data of this study are narrator’s explanations and the characters’ utterances related the symptoms of the personality disorder suffered by Anna only. This study found that the personality disorder suffered by Anna is borderline personality disorder. This study is intended to explain the symptom of borderline personality disorder experienced by Anna are the instability in her mood and behavior and the fear of abandonment and the instability in her interpersonal relationships.